Constrictive Pericarditis: Modern Causes of an Old Disease - Gargoum, Hassan A. (Libyan International Medical University Journal, 2025)
This review examines the evolving landscape of constrictive pericarditis (CP) through analysis of literature spanning 1932 to 2025, sourced from PubMed, Scopus, and Google Scholar using key terms related to the etiology, clinical features, diagnosis, and treatment of CP. Eligible literature included original research articles, systematic and narrative reviews, case reports, expert consensus statements, and guidelines from professional societies. CP is a chronic pericardial disease resulting in impaired ventricular filling and heart failure symptoms. While previously dominated by tuberculosis and idiopathic cases, its modern etiological profile has shifted significantly. This review explores the evolving causes, clinical features, diagnostic advances, and treatment strategies of CP in the current medical practice. Modern causes of CP include prior cardiac surgery/percutaneous intervention, radiation therapy, autoimmune diseases, viral pericarditis, and uremia associated with end-stage renal disease. Modern imaging modalities—particularly echocardiography, cardiac computed tomography, and cardiac magnetic resonance imaging—have improved diagnostic accuracy and helped differentiate CP from other causes of heart failure. Features such as pericardial late gadolinium enhancement and elevated inflammatory markers help identifying reversible subset of the disease, which may respond to anti-inflammatory therapy. In chronic, fibrotic cases, surgical pericardiectomy remains the definitive therapy, with outcomes improved by early diagnosis and appropriate timing of surgery. CP is no longer a relic of the past, but a dynamic condition shaped by modern medicine. Recognizing its evolving etiologies is critical for timely diagnosis and individualized treatment. With advances in imaging and inflammation-targeted therapies, opportunities exist to improve outcomes and reduce reliance on surgery in selected cases.
Keywords: constriction; CP; pathophysiology; pericardial disease; pericarditis